Influence of the starting time of preslaughter feed withdrawal on welfare of pigs and pork quality - Dalla Costa, Filipe Antonio [UNESP] (2016)
The objective of this study was to evaluate the effects of starting time of feed withdrawal interval preslaughter at the farm (FARM) or at the plant (PLANT) on animal losses, behaviour during loading and lairage, blood parameters (lactate and creatine kinase) and meat quality traits (pH, colour and drip loss) in pigs. A total of 700 pigs was distributed into two treatments groups. The FARM group was fasted for 18 h before the transport plus 6 h before slaughter, including 2 h transport and 4 h lairage, and the PLANT group was fasted for 24 h (considering 2 h transport plus 22 h at lairage), totalizing 24 h of fasting time before slaughter for both groups. The treatments neither influenced transport losses nor blood parameters. However, PLANT pigs had longer fights (P < 0.05) than FARM pigs at lairage and produced darker (P = 0.02) and drier (P = 0.03) loins. Based on these results, it is recommended apply feed withdrawal time before loading, which showed improvements to pigs’ welfare, due to the lower number of fights during lairage at the slaughter plant, and produced better pork quality.